The impact of Sustainable Forest Management (SFM) practices on primary timber-based production in Peninsular Malaysia - Noraida A.W.,; Abdul-Rahim A.S.,; Mohd-Shahwahid H.O., (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper investigates the impact of Sustainable Forest Management (SFM) practices on primary timber-based production in Peninsular Malaysia that is complying with the SFM practice scenarios. The Autoregressive Distributed Lagged (ARDL) Bounds Testing Approach have been used to analyze time series data from 1980 to 2012. Four scenarios were investigated: (i) 24% reduction in the harvested area, (ii) 25%increase in the domestic price of commodities, (iii) 47%increase in input costs, and (iv) a combination of Scenarios i, ii, and iii. The results reveal that sawn timber production is positively affected by the SFM practices; these practices vary between veneer and plywood production. Consequently, the producer can enhance sawn timber production after imposing the SFM practice scenario. The SFM practice scenario would generate the sustainable growth of the timber-based industry and help to enhance Peninsular Malaysia’s forest conservation goals.